The ABC of crop insurance as a risk management tool: A manual for farmers - Murabula, Sarah; Hientz, Lennart; Binge, Brenda; Mwongera, Caroline; Muriithi, Cyrus K; Kinyua, Ivy Wambui; Osiemo, Jamleck (2023)
The Innovation for Africa Climate Risk Insurance, InACRI project, addresses the current poor performance and uptake of index-based crop insurance products in Kenya. As part of the outputs to improve adoption the project developed a farmer guide to provide them with information on crop insurance such as the advantages of crop insurance, types of crop insurance, what to consider when choosing an insurance policy, the claims process, and the costs associated with crop insurance. This guide is brief and comprehensive with three main objectives 1)To enhance your understanding of crop insurance for better decision making 2)To simplify crop insurance and related concepts. 3)To increase your awareness of the role of crop insurance in agricultural risk management.